Dehydration of traditional dried instant noodle (mee siput) using controlled temperature & humidity dryer - Mamat, K. A.; Yusof, M.S.; Wan Yusoff, Wan Fauziah; Rahim, M. Zulafif; Hassan, S.; A. Rahman, M. Qusyairi; Abd Karim, M. A. (IOP Publishing, 2017)
Drying process is an essential step to produce instant noodles. Yet, the industries especially Small and Medium Enterprises (SMEs), is seeking for an efficient method to dry the noodles. This paper discusses the performance of an invented drying system which employed heating and humidifying process. The drying system was tested using 30 kilogram of the raw noodle known as “Mee Siput”. Temperature controlled system were used in the study to control the temperature of the drying process and prevent the dried noodles from damage by maintaining the temperature of lower than 80oC. The analysis shows that the system was drastically decreased the humidity from 80% to 40% just after 200 minutes of the drying process. The complete dehydration time of noodle has also decreased to only 4 hours from 16 hours when using traditional drying system without sacrificed the good quality of the dried noodle. In overall, the invented system believed to increase the production capacity of the noodle, reduce cost of production which would highly beneficial for Small Medium Industries (SMEs) in Malaysia.